Analysis of Nursing Care Documentation on the Performance of Nurses in the Inpatient Room of Muhammadiyah Hospital Ahmad Dahlan Kediri - Dwi Wulan Ningtyas; Muhamad As'ad Efendy (PT. Griya Eka Sejahtera, 2020)
Background: The behavior of a nurse related to performance is related to nursing tasks that must be carried out, this is the importance of recording nursing care documentation and improving nurse performance in health services. Method: This study aims to identify the analysis of nursing care documentation on the performance of nurses in the inpatient room at RSM Ahmad Dahlan, Kediri. The sampling technique used stratified random sampling to obtain a sample of 56 respondents. This type of research is quantitative using the Spearman rank test. Data collection using a questionnaire. Results: The results showed that of the 56 respondents, most of them had adequate nursing care documentation, 44 respondents (79%), most of them had good nurse performance as many as 32 respondents (57%). Conclusion: The results of the Spearman Rho statistical test have a significance value of <0.05 with a significance result of 0.038, which means that it can indicate that there is a relationship between nursing care documentation and the performance of nurses in the inpatient room at RSM Ahmad Dahlan Kediri